PENGEMBANGAN USAHA SAYURAN DAUN SINGKONG UNTUK PEMENUHAN KEBUTUHAN DAPUR UNIDA DAN RUMAH MAKAN PADANG BAGI UPT AGROTEKNOLOGI - Isnatin, Umi; Etica, Use (Jurnal Terapan Abdimas, 2021)
Abstract. The Technical Implementation Unit of agrotechnology as an entrepreneurial development for the student of agrotechnology at the University of Darussalam Gontor has a problem at the managerial level. The management indicator referred to is cultivation management, finance, and marketing. Therefore, this research emphasizes the program on improving students' managerial abilities for 4 months. The purpose of this study is as a means of learning for students in cultivating cassava plants for entrepreneurship. One thing that must be improved is the cultivation of cassava leaves and how to market them. Furthermore, the availability of cassava leaves (Manihot utilisima) refers to the production of cassava plants, and up until this point, there is no special cultivation for cassava leaves. The method used in this research is the practice of cultivating cassava and holding training in making Bhokasi and POC fertilizers, training in making vegetable pesticides, training for post-harvest and product packaging. This service activity will help to succeed in improving student skills as well as practicing cassava cultivation and building marketing networks in the UNIDA Gontor's business units and Padang restaurant as one of the restaurants that use cassava leaves the most.  Abstrak. UPT Agroteknologi sebagai lokasi pengembangan kewirausahaan mahasiswa prodi Agroteknologi Universitas Darussalam Gontor masih belum maksimal dalam pengelolaan. Indikator pengelolaan yang dimaksud adalah pengelolaan managemen budidaya, keuangan dan pemasaran. Pengabdian  kami fokuskan pada program  peningkatan kemampuan   mahasiwa selama 4 bulan. Tujuan dari kegiatan ini sebagai sarana belajar mahasiswa dalam budidaya tanaman singkong yang akan diambil daunnya dan wirausaha. Salah satu yang akan kita tingkatkan adalah   budidaya daun singkong dan cara pemasarannya. Daun singkong (Manihot utilisima), selama ini ketersediaannya mengacu kepada produksi tanaman singkong, dan belum ada budidaya khusus untuk sayur daun singkong. Adapun metode kegiatan yang kami lakukan adalah praktek budidaya tanaman singkong dan mengadakan pelatihan pembuatan pupuk Bhokasi dan POC, pelatihan pembuatan pestisida nabati, pelatihan pasca panen dan pengemasan produk. Kegiatan pengabdian ini berhasil peningkatkan kemampuan mahasiswa sekaligus praktek budidaya tanaman singkong dan membangun jaringan pemasaran di dapur UNIDA Gontor dan Rumah Makan Padang. .